The adoption of Fintech applications in wealth banking - Nel, Pierre Retief (University of the Free State, 2023)
Financial technology, or FinTech, offers substitutes for some products used in traditional banking and non-banking finance services. In the financial sector, FinTech is a new idea. This field study’s main goal is to gain insight into wealth clients' perspectives of FinTech adoption within a wealth banking paradigm. It explains the factors that affect how clients perceive using FinTech services in the wealth management industry. The wealth management services industry's traditions and behaviour will alter as well as how AI will be adopted, different generations and population to name a few. This study explored further into the factors that influence wealth clients’ perceptions when adopting FinTech services as part of a large South African bank's wealth management client base. Due to technological advancements, the financial world has been changing quickly, and practically every facet of it now has a new look and feel. FinTech is the term used to describe this technological transformation in the financial sector. Even if the ‘FinTech influence’ has been felt throughout all financial services, the wealth management business is just beginning to experience it in comparison to other financial services industries. The clientele of wealth management is ageing, and younger people and women are significantly underrepresented. Despite the younger populations' interest in FinTech solutions, the wealth services sector currently provides only a few possibilities for them. The distribution of female clients in wealth management is lagging behind overall growth trends. Wealthy customers use a variety of wealth service providers, combine different wealth service options, and maintain a strong personal connection with either their wealth banker, investment manager, or both. FinTech services help wealth management clients operate more effectively while also increasing their usefulness and meeting their needs for services. Financial management clients employ FinTech service offerings from only well-known wealth service providers with confidence. South Africa's wealth management industry lags the US and UK's by several years. Currently, FinTech is seldom present in the core wealth management industry. In the South African wealth market, there aren't many entry-level Robo-advisors, but those that do exist don't pose much of a threat to the market leaders. Wealth management should acknowledge the impact of technology advancements on client behaviour. Ensuring a trusted relationship for wealth management is high priority in evaluating the bank/client relationship when incorporating or planning FinTech services in wealth banking. Also, to understand what drives client perception in relationship quality and how these perceptions need to be combined to find the right balance of quality. It is important for the wealth management business to understand the risk of an aging book and to implement proper wealth transfer strategies to include the next generation. With a diversified and growing investment market with increasing options, wealth management need to look at how they can deliver alternative asset classes to add value to a growing and more diversified client base. Managing complexity such as volatility, and the risk of various different asset classes, might be in the form of robo-advisors. Wealth management need to find the FinTech ‘disruptor’ of the status quo. Overall, FinTech has improved the services offered by the traditional wealth management sector. Wealth management need to accept the future lies in a fully digital FinTech platform that serves as a one-stop shop for all wealth management needs. Digital and online engagement is the future of the wealth management industry and wealth technology. The current nature of advice professionals will evolve, becoming a more individualised one-stop solution thanks to the more sophisticated client interaction digital platforms. South Africa's banking system is in a state of flux and change. On one hand, traditional banking models have seen a decrease in market share as fintech innovations have gained traction within the country. On the other hand, fintech has had its own struggles, with many South Africans still not having access to digital banking services. Fintech refers to the use of technology to offer financial services, including mobile banking, online banking, and digital wallets.
Dissertation (MBA (Business Administration))--University of the Free State, 2023
Keywords: FinTech adoption factors; intention to adopt fintech; wealth banking; wealth management; wealthtech; Robo-advisor; TAM model